Dampak Kuliah Sambil Bekerja Terhadap Indeks Prestasi Mahasiswa Perguruan Tinggi Negeri Dan Swasta di Kabupaten Jember Tahun 2017 - Suwarso Suwarso (STIE Mandala Jember, 2018)
This study aims to determine the Impact of Lectures While Working Against Achievement Index of State and Private University Students in Jember District in 2017. This research is qualitative by presenting the intreview results in the field. Samples taken are 20 students of State and Private Universities in Jember. The results of this study, the average student who runs college while working is the increase in student achievement index. This means that the impact of students who lectured while working quite positive role in getting the Achievement Index during the lecture process took place. In addition to the increase in Achievement Index, other impacts arise include independence and experience. Keywords: Achievement Index, Student, Work.